On the roles of organic acids transport and sucrose metabolism controlling stomatal movements - Medeiros, David Barbosa (2017)
Regulation of the stomatal movements by osmotic control is a well-documented mechanism that is associated to the transport of solutes coupled with changes in the guard cell metabolism. Potassium and chloride are the main inorganic ions whereas malate and sucrose (Suc) are the main organic osmolytes involved in stomatal movements. Despite the growing body of information concerning the control of stomatal movements, there are, however, several gaps regarding the stomata regulation to be fully elucidated. Thus, understanding stomatal behaviour represents an important step towards enhancement of water use efficiency in plants. Several efforts have been performed to fully characterize the events that occur in guard cells. Experimental data describing distinct aspects of stomatal behaviour have been presented, providing significant insights into guard cell transcriptome, proteome, and metabolome. In this thesis I, initially, revisited the current available omics studies and modelling in guard cells. By doing that, it was possible to demonstrate that the current modelling approaches describe the stomatal conductance in terms of relatively few easy-to- measure variables being unsuitable for in silico design of genetic manipulation. Therefore, we discuss that system biology approach combining modelling and high-throughput assays may be used to elucidate the mechanisms underlying stomatal control allowing a better prediction of phenotypes in the field. Additionally, to obtain a more comprehensive picture of the function of organic acid transport and sucrose metabolism during stomatal movements, three independent but complementary experimental approaches were used to: (i) characterise mutant plants lacking the organic acids channel located at the guard cell plasma membrane (AtQUAC1); (ii) analyse the effects on stomatal behaviour, photosynthetic capacity, and the metabolism due to impaired malate and fumarate accumulation in Arabidopsis leaves; (iii) to investigate the effects of sucrose on the stomatal aperture and the carbon flux during stomatal opening by using stomatal aperture assays and isotope labelling kinetic experiments. Briefly, the results presented here provided several novel findings. Firstly, the inefficient stomatal closure via the repression of AtQUAC1 culminates in higher growth and photosynthetic rates through increased mesophyll and stomatal conductance, followed by changes in organic acids and sugars accumulation in leaves. Secondly, impaired malate and fumarate accumulation throughout the diel cycle in attdt mutants strongly affected mitochondrial metabolism but not plant growth without any impact in both stomata kinetics and photosynthesis. Thirdly, the role of sucrose during stomatal opening was demonstrated to be dose-dependent whilst sucrose is degraded within guard cells during light-induced stomatal opening. Collectively, the results obtained here demonstrate the complex interaction between guard cells and mesophyll and also highlight the role of the mesophyll metabolism as an important player controlling guard cell movements. I further discuss these observations in the context of the current knowledge concerning the metabolic control of stomatal movements, central carbon metabolism, and plant performance.